Here there and everywhere - MURTY (Sudha) (USA Penguin Books, 2018)
Wearer of many hats-philanthropist, entrepreneur, computer scientist, engineer, teacher-Sudha Murty has above all always been a storyteller extraordinaire. Winner of the R.K. Narayan Award for Literature, the Padma Shri, the Attimabbe Award from the government of Karnataka for excellence in Kannada literature, and the Raymond Crossword Lifetime Achievement Award, her repertoire includes adult non-fiction, adult fiction, children's books, travelogues and technical books. Here, There and Everywhere is a celebration of her literary journey and is her 200th title across genres and languages. Bringing together her best-loved stories rom various collections alongside some new ones and a thoughtful introduction, here is a book that is, in every sense, as ltifaceted as its author.